Panorama Des Maladies Rhumatismales A Conakry - Kamissoko Aly Badra; Diallo Mamadou Lamine; Traoré Marie; Diallo Alhassane; Yombouno Emmanuel; Barry Abdoulaye; Touré Moriba; Awada Mohamed; Oniankitan Owonayo (European Scientific Journal, ESJ, 2018)
Objective: To determine the epidemiological profile of rheumatic diseases in hospital consultation at the Ignace Deen National Hospital in Conakry (Guinea). Patients and methods: We used a cross-sectional study of participant seen in rheumatologic consultation between November 1, 2016 and November 30, 2017 at the Rheumatology Department of the Ignace Deen National Hospital in Conakry (Guinea). Rheumatic diseases were diagnosed according to the rigorous criteria. Results: We collected 1038 patients including 679 women (65.41%). The mean age of the patients was 49.88 ± 17.47 years with range of 5 and 93 years. Degenerative pathology (644 cases, 62.04%), chronic inflammatory rheumatism and connective tissue diseases (252 cases, 24.27%), periarticular pathology and canal syndromes (91 cases, 8.76%), microcrystalline arthropathies (49 cases, 4.72%), osteopathies (45 cases, 4.33%), and infectious diseases (16 cases, 1.54%) were the main disorders observed during study period. Conclusion: Most of the rheumatic diseases described in the literature have been found. The particuliarity was the relative frequency of inflammatory rheumatism and fracture osteoporosis. However, the further epidemiological studies would be needed to confirm these data.